Quality assessment of research studies on microplastics in soils: a methodological perspective - Shanmugam, Shyamala Devi; Praveena, Sarva Mangala; Sarkar, Binoy (Elsevier, 2022)
Microplastics have become a global concern, and soil acts as a major sink for plastic pollution. Due to rapid development of soil microplastics research, various analysis methods have been developed, but require proper consistency and standard procedures. The objective of this study was to appraise a quality assessment concerning soil microplastics from a methodological perspective. Nine studies were selected for the quality assessment exercise based on methodological investigations on soil microplastics and were evaluated based on the adapted Criteria for Reporting and Evaluating Ecotoxicity Data (CRED) method. The highest score obtained by an individual study was 21 while the lowest was 14, leaving a wide score gap which indicated inconsistency amongst the studies. Criterion with the highest average score of 2.0 was obtained for sample size and data reporting. The lowest average score of 0.89 was for the negative control. In conclusion, the total average scores for all eleven criteria were 1.56. Current quality assessment perceived that there was room for improvement and betterment of quality assurance for studies on microplastics and a form of guideline on methodological aspects of soil microplastics studies. It was suggested that future microplastics studies should methodically include quality assurance/quality control (QA/QC) protocols in every process to ensure that good quality data is produced and applied in the risk assessment process.